Performance Evaluation of Four Wheel Tractor Driven High Capacity Combined Paddy Thresher - GVTV Weerasooriya; MHMA Bandara; M Rambanda (Tropical Agricultural Research, 2011)
Lower performances of traditional threshing methods, labour shortage, reduced turn-around time and use of high yielding varieties have inevitably forced farmers to shift into mechanical grain threshing. Recently introduced four-wheel tractor driven high capacity combined paddy thresher gained popularity among Sri Lankan farmers. However, this thresher has not been properly evaluated. This study evaluated the field performances and economics of this thresher and monitored the emission of chaff and dust to compare the commercial makes, grain types and operational conditions. This study was carried out in the North Central Province of Sri Lanka, during the Maha season of 2008/2009. Air monitoring on inhaled air was done by filtration technique, using special masks and surrounding environment by gravity techniques, using Polyurethane foam. As per the RNAM test code procedures, three commercial makes of high capacity combined paddy threshers were evaluated under different operational conditions for long and short grain paddy varieties with two replicates. The combined paddy threshers showed 1.8% damaged grain, 0.2% blown grains, 1.6% grain losses, 96.7% threshing recovery, 98.8% threshing efficiency, 90.7% cleaning efficiency, 1178 kg/h corrected output capacity and Rs. 2744 actual cost of threshing per metric ton of output at 14% moisture content. Though this thresher is suited for Sri Lankan conditions, it is associated with considerable amount of chaff and dust content such as; 2.04 mg/cm2/h in inhaled air and 35.59 mg/cm2/h in surrounding environment. The performance, economics and chaff and dust emission vary with make of the machine, grain type and operational conditions. Grain moisture is the most dominantly affected factor for the thresher performance. Keywords: Chaff; dust; paddy; threshing DOI: http://dx.doi.org/10.4038/tar.v22i3.3700 Tropical Agricultural Research 22(3) (2011) 273-281